Analysis of the Clinical Pipeline of Treatments for Drug-Resistant Bacterial Infections: Despite Progress, More Action Is Needed - Butler, Mark S.; Gigante, Valeria; Sati, Hatim; Paulin, Sarah; Al-Sulaiman, Laila; Rex, John H.; Fernandes, Prabhavathi; Arias, Cesar A.; Paul, Mical; Thwaites, Guy E.; Czaplewski, Lloyd; Alm, Richard A.; et al. (Antimicrobial agents and chemotherapy, 2022)
There is an urgent global need for new strategies and drugs to control and treat multidrug-resistant bacterial infections. In 2017, the World Health Organization (WHO) released a list of 12 antibiotic-resistant priority pathogens and began to critically analyze the antibacterial clinical pipeline. This review analyzes “traditional” and “nontraditional” antibacterial agents and modulators in clinical development current on 30 June 2021 with activity against the WHO priority pathogens mycobacteria and Clostridioides difficile . There is an urgent global need for new strategies and drugs to control and treat multidrug-resistant bacterial infections. In 2017, the World Health Organization (WHO) released a list of 12 antibiotic-resistant priority pathogens and began to critically analyze the antibacterial clinical pipeline. This review analyzes “traditional” and “nontraditional” antibacterial agents and modulators in clinical development current on 30 June 2021 with activity against the WHO priority pathogens mycobacteria and Clostridioides difficile . Since 2017, 12 new antibacterial drugs have been approved globally, but only vaborbactam belongs to a new antibacterial class. Also innovative is the cephalosporin derivative cefiderocol, which incorporates an iron-chelating siderophore that facilitates Gram-negative bacteria cell entry. Overall, there were 76 antibacterial agents in clinical development (45 traditional and 31 nontraditional), with 28 in phase 1, 32 in phase 2, 12 in phase 3, and 4 under regulatory evaluation. Forty-one out of 76 (54%) targeted WHO priority pathogens, 16 (21%) were against mycobacteria, 15 (20%) were against C. difficile , and 4 (5%) were nontraditional agents with broad-spectrum effects. Nineteen of the 76 antibacterial agents have new pharmacophores, and 4 of these have new modes of actions not previously exploited by marketed antibacterial drugs. Despite there being 76 antibacterial clinical candidates, this analysis indicated that there were still relatively few clinically differentiated antibacterial agents in late-stage clinical development, especially against critical-priority pathogens. We believe that future antibacterial research and development (R&D) should focus on the development of innovative and clinically differentiated candidates that have clear and feasible progression pathways to the market.